Physiological Functions of Threonine in Animals: Beyond Nutrition Metabolism - Qi Tang; Peng Tan; Ning Ma; Xi Ma (2021)
Threonine (Thr), an essential amino acid for animals and the limiting amino acid in swine and poultry diets, which plays a vital role in the modulation of nutritional metabolism, macromolecular biosynthesis, and gut homeostasis. Current evidence supports that the supplementation of Thr leads to benefits in terms of energy metabolism. Threonine is not only an important component of gastrointestinal mucin, but also acts as a nutritional modulator that influences the intestinal immune system via complex signaling networks, particularly mitogen-activated protein kinase (MAPK) and the target of the rapamycin (TOR) signal pathway. Threonine is also recognized as an indispensable nutrient for cell growth and proliferation. Hence, optimization of Thr requirement may exert a favorable impact on the factors linked to health and diseases in animals. This review focuses on the latest reports of Thr in metabolic pathways and nutritional regulation, as well as the relationship between Thr and relevant physiological functions.